Of Human Sacrifice and Barbarity: A Case Study of the Late Archaic Tumulus XVII at Istros - Fowler, Michael (História: Questões & Debates, 2021)
This article consists of a close examination of one of four Late Archaic-era tumular monuments that were excavated in the mid-1950s in the Northern Necropolis of the Pontic Greek settlement of Istros. The exploration of this monument, Tumulus XVII (circa 550-525 BCE), yielded several features that were immediately compared with heroic cremation burials as described in epic poetry (particularly the funeral of Patroklos in Homer’s Iliad). Most striking among these features were the remains of three human sacrificial victims. Despite the early connection drawn with Homeric epic, for the next three decades Tumulus XVII was classified as a non-Greek (Thracian) monument, principally due to the presence of human sacrifice. That is, human sacrifice was regarded as too primitive and thus foreign to the more ‘advanced’ Greek culture. For this reason, the evidence from Istros has not figured prominently in synthetic studies of Greek human sacrifice. Yet, the growing body of research into Greek and indigenous settlements and cemeteries in the western Black Sea, along with the more recent discovery of a bound and ritually decapitated man alongside Pyre A at Orthi Petra (circa 700 BCE; Eleutherna, Crete), has occasioned a reconsideration of the original barbarian characterization of Tumulus XVII. The funerary rituals and resulting tumular monument rather appear to have been developed by an elite subset of the Greek colonial community as a means to distinguish and elevate themselves among the ever-growing population of the city. While epic may have lent general inspiration and significance to the particular rituals performed, a more immediate model for the tumular form may have been taken from the ‘heroon’ (late 7th cent. BCE) in the necropolis of the nearby Greek settlement of Orgame. Although the precise circumstances surrounding the funerary human sacrifices elude us, this short-lived ritual phenomenon seems rather to have been introduced to the region by Greek settlers.